Pengaruh Progressive Muscle Relaxation (PMR) terhadap Myalgia pada Pasien Kanker Paru yang Menjalani Kemoterapi - Komalawati, Dedeh (Sekolah Tinggi Ilmu Kesehatan RS Husada, 2018)
Myalgia can be occured by side effect of chemotherapy. The purpose of this study was to identify the effect of PMR against myalgia in lung cancer patients undergoing chemotherapy. This study design was a quasi experiment, used pre and post test with control group. Samples were 32 patients, recruited by consecutive sampling. Measuring pain assessment used numeric rating scale. The intervention group had been provided PMR fifteen minutes twice a day for five days post chemotherapy. The results showed significantly different reduction of pain intensity before and after providing PMR in the intervention group and control group as well (p value = 0,001). There was a significantly different reduction of myalgia intensity between both group after giving intervention with mean difference 0,81 (p value = 0,001). It can be concluded that PMR can reduce myalgia in lung cancer patients undergoing chemotherapy. Suggestion, PMR becomes one of the complementary therapies to overcome myalgia